Correlations between plantar pressure and postural balance in healthy subjects and their comparison according to gender and limb dominance: A cross-sectional descriptive study - Arin-Bal, Gamze; Livanelioglu, Ayse; Leardini, Alberto; Belvedere, Claudio (Gait & posture, 2024)
Lower extremity injuries rank among the most common injuries affecting young population, and numerous factors affect the outcomes of plantar pressure and balance assessment. Does a correlation exist between plantar pressure and postural balance in healthy subjects and are there any difference in the results based on gender and limb dominance? This study involved thirty healthy recreationally active young adults (15 females, 15 males). Plantar pressures were analyzed using the MatScan Pressure Mat System, and postural balance was evaluated using Biodex Balance System. All assessments conducted under both static and dynamic conditions. Correlations were tested by Spearman Correlation Coefficient, and comparative tests were performed for gender and limb dominance. Correlations were observed between plantar pressure parameters and balance scores, particularly in the dynamic conditions (p < 0.05). Gender-based differences were noted in plantar pressure parameters (p < 0.05), with females demonstrating improved balance stability scores. No significant differences were found based on limb dominance in plantar pressure and postural balance data (p > 0.05). This study provides valuable detailed insights into the existing literature concerning plantar pressure and postural balance assessments within the healthy population. A strong correlation was observed between plantar pressure and postural balance, and the comparisons of these assessments were affected by gender but not by limb dominance. These results could lead the way for better rehabilitation approaches by considering the correlations and differences across diverse populations. •Plantar pressure parameters in young healthy adults are correlated with postural balance scores.•Plantar pressure and postural balance variables are affected by gender.•Limb dominance has no effect on plantar pressure and postural balance variables.